Technical report on safe and sustainable vegetable production activities in Benin - Legba, Eric; Dossou, Laurence; Honfoga, Judith; Ramasamy, Srinivasan (International Food Policy Research Institute, 2023)
Agriculture is the main activity employing up to 70% of the working population in Benin. It contributes an average of 32.5% to the Gross Domestic Product (GDP), 75% to export earnings, and 15% to government revenue (PSRSA, 2016). Benin's agriculture comprises a set of crops, among which vegetable crops constitute one of the strategic sectors and an important agricultural industry that employs thousands of people across urban, peri-urban, and rural areas (ACED, 2020). Vegetable production is crucial to the region's food security and poverty alleviation. It is a vital income generation activity and contributes to the livelihoods of many people in Benin. For example, PADAP (2003) reported that only the vegetable sector creates 60,000 direct jobs and 25,000 indirect jobs for Benin citizens. To promote vegetable production and consumption in Benin, efforts are being made to address challenges related to production technology, efficiency, marketing, and food safety. The SAFEVEG program, for example, aims to improve the production, marketing, and intake of vegetables in Benin, Burkina Faso, and Mali. In addition, CGIAR Research Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH) aims to develop, test, and scale up new technologies using the "End to End" approach. The objective of the FRESH project is to sustainably increase Fruit and Vegetable intake and improve diet quality, nutrition, and health while also improving livelihoods in selected countries by empowering women and youth and creating. The project started in May 2022 and is structured in 6 works packages (WP): (1) Consumer Behavior Analysis; (2) Biodiversity, Genetic Innovation, and Seed Systems; (3) Sustainable Fruit and Vegetable Production System; (4) Post-Harvest and Markets; (5) Food Environment; and (6) Policy Environment and Impact Assessment.